2011
DOI: 10.5897/ajpp11.136
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic and antioxidant activity of Viscum album extract

Abstract: The antihyperglycemic and antioxidant effects of water extract of local Viscum album in alloxanizedrats were investigated. This study performed during 2009 in Babol University of medical sciences (Mazandaran Province, Iran). V. album leaves growing on oaks collected and extracted with hot water. The 90 animals that were used in this investigation were male Wistar rats. 60 rats were gavaged with 500 and 1000 mg/kg/day of V. album extract. One hour after final feeding, freshly prepared alloxan injected subcutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 13 publications
3
18
0
Order By: Relevance
“…It has also been demonstrated that active constituents are heat resistant (Gray & Flatt 1999). A significant decrease in serum glucose level accompanied by an increase of the serum insulin level was observed in alloxan-hyperglycaemic rabbits and rats after administration of mistletoe water extract (Ohiri et al 2003;Shahaboddin et al 2011). The extract enhanced the serum's antioxidant activity which is very important in the prevention of diabetic complications (Shahaboddin et al 2011).…”
Section: Antidiabetic Propertiesmentioning
confidence: 96%
“…It has also been demonstrated that active constituents are heat resistant (Gray & Flatt 1999). A significant decrease in serum glucose level accompanied by an increase of the serum insulin level was observed in alloxan-hyperglycaemic rabbits and rats after administration of mistletoe water extract (Ohiri et al 2003;Shahaboddin et al 2011). The extract enhanced the serum's antioxidant activity which is very important in the prevention of diabetic complications (Shahaboddin et al 2011).…”
Section: Antidiabetic Propertiesmentioning
confidence: 96%
“…Likewise, rats fed by gavage with 500 and 1000 mg/kg/day of Viscum album extract for 72 h caused significant (p < 0.05) reduction in blood glucose and increased antioxidant power of alloxanized rats. [68] These findings indicate that the route and mode of drug administration alters the level of drug delivery and efficacy.…”
Section: Discussionmentioning
confidence: 92%
“…[38][39][40][41] The Figure 1. Erythrocyte glutathione S-transferases activity of hyperglycemic rats with/without glycemic control.…”
Section: Discussionmentioning
confidence: 99%